Review paperNeurogenesis and neuroprotection in postischemic brain neurodegeneration with Alzheimer phenotype: is there a role for curcumin? - Pluta, Ryszard; Bogucka-Kocka, Anna; Ułamek-Kozioł, Marzena; Furmaga-Jabłońska, Wanda; Januszewski, Sławomir; Brzozowska, Judyta; Jabłoński, Mirosław; Kocki, Janusz (Folia Neuropathologica, 2015)
For thousands of years, humankind has used plants for therapeutics. Nowadays, there is a renewed public interest in naturally occurring treatments with minimal toxicity and diets related to health. Alterations in hippocampal neurogenesis have been recognized as an integral part of brain ischemia. Neuronal stem/progenitor cells in the hippocampus are positively and negatively regulated by intrinsic and extrinsic agents. One positive regulator of neurogenesis in the hippocampus is curcumin in the diet. This review provides an assessment of the current state of the field in hippocampal neurogenesis and neuroprotection studies in brain ischemia and focuses on the role of curcumin in the diet. Data suggest that dietary intake of curcumin enhances neurogenesis. Recent studies performed in ischemic models have suggested that curcumin also has neuroprotective features. One potential mechanism to explain several of the general health benefits associated with curcumin is that it may prevent ageing-associated changes in cellular proteins that lead to protein insolubility and aggregation after ischemia such as β-amyloid peptide and tau protein. Here, we also review the evidence from ischemic models that curcumin improves cognition and health span by overexpression of life supporting genes and preventing or delaying the onset of neurodegenerative changes. Available data provide evidence that curcumin induces neurogenesis and neuroprotection and may provide a novel therapeutic agent for both regenerative medicine and for the treatment of neurodegenerative diseases such as postischemic brain neurodegeneration with Alzheimer phenotype.